The Italian Museo Nazionale dell’Antartide: national and international contribution to education, outreach and training - Orombelli, G.; Albertelli, G.; Bernat, P.; Cattadori, M.; Faranda, F. M.; Folco, L.; Müller, J.; Olmastroni, S.; Ossola, C.; Povero, P.; Palmeri, R.; Ricci, C. A.; et al. (SCAR, 2012)
The Italian Museo Nazionale dell’Antartide (www.mna.it) was established as a consortium of three universities (Genova, Siena, Trieste) in 1996 with the aim to preserve, study, and increase the value of all material collected during the Italian Antarctic scientific expeditions, as well as to promote public understanding of scientific results. All three sections hold a permanent exhibition to promote the knowledge of the Antarctic continent. The Genova section is dedicated to biology and ecology, Siena to Earth sciences and Trieste to history of exploration and marine geology. The contribution of the museum to education, outreach and training is devoted to promote the polar knowledge to schools through lectures, guided visits and didactic laboratories to all-level students, from kindergarten to PhD level. Recent and ongoing initiatives are: - travelling exhibition - support to the PhD school on polar science - polar summer school for teachers - organization of workshops and congresses on polar topics, climate change, extreme environments; - editing of proceedings and special issues of scientific journals - theatrical performances on the exploration of Antarctica.